English - have a go : - Nery, Caryn. (Oxford University Press, 1996)
The series, through the life of the Jones family, presents grammar, pronunciation and useful sentences for learners of English. There is also a segment introducing Australian families, including families from Korean, Italian, Chinese, English, Aboriginal and Greek backgrounds.